Differences, links, and roles of microbial and stoichiometric factors in microplastic distribution: A case study of five typical rice cropping regions in China - Yao, Yao; Wang, Lili; Gong, Lingxuan; Li, Gang; Xiu, Weiming; Yang, Xiaomei; Tan, Bingchang; Zhao, Jianning; Zhang, Guilong (Frontiers in Microbiology, 2022)
Microplastics (MPs), as new pollutants in agroecosystems, have already attracted widespread attention from scientists. However, our understanding of MP geographic distribution and its influencing factors across spatial scales remains poor. Here, a regional-scale field investigation was conducted to assess the distribution characteristic of MPs in five major rice-growing regions of China, and we explored the roles of biological and abiotic factors, especially stoichiometry and microbial influences on MP distribution. MPs were observed in all sampling sites, averaging 6390 ± 2031 items·kg-1. Sizes less than 0.5 mm and black and transparent MPs dominated. Fiber, classified as one of the MP shapes, occurred most frequently. MP community analysis, firstly used in paddy soil, revealed more black MPs abundance in HE, more rayon, blue, and other colors MPs in HN, more transparent MPs in TJ, and more PE MPs in DB. Higher MP community diversity was found in most south paddy soils of this study, due to a broader range of sources. C/N showed a positive relationship with pellet-shaped MP abundance and MPs of size between 2 mm to 5 mm (P < 0.05). Chao1 index of soil microbial communities was positively correlated with the MP abundance, MPs of size less than 0.5 mm, and fiber abundance. The minimum temperature was positively correlated with MP abundance (P < 0.05), implying the potential effects of the freeze-thaw process might exist. The regression analysis highlighted the important role of population quantity in determining MP abundance (R = 0.421, P = 0.02). This study confirmed the wide distribution of MPs in different soil depths of paddy lands in China and demonstrated that its distribution was influenced by population quantity and environmental variables, such as microbiology. These findings could provide a basis for the toxicological behavior of MPs and the potential risk to human health.